(-4.5,6y+1-3y=-17)

Simple and best practice solution for (-4.5,6y+1-3y=-17) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-4.5,6y+1-3y=-17) equation:



(-4.5.6y+1-3y=-17)
We move all terms to the left:
(-4.5.6y+1-3y-(-17))=0
We calculate terms in parentheses: +(-4.5.6y+1-3y-(-17)), so:
-4.5.6y+1-3y-(-17)
determiningTheFunctionDomain -4.5.6y-3y+1-(-17)
We add all the numbers together, and all the variables
-5.7y+18
Back to the equation:
+(-5.7y+18)
We get rid of parentheses
-5.7y+18=0
We move all terms containing y to the left, all other terms to the right
-5.7y=-18
y=-18/-5.7
y=3+0.9/5.7

See similar equations:

| 6r–1+6r=11 | | 3(10x-x)=60-x | | -4x-23=-6 | | -12v+3v=-9(1+9v)+9(4v-7) | | -0.03x=-525 | | 9(2r+4)=-9(-4+10r)+10r | | (7-x)*(10-x)+54=0 | | 8x+8+5x-25=180 | | -4(2y+1)=36 | | 2k-5+3k=k+6 | | x^2+17x-124=0 | | 5x+2(x-3)-1=21 | | -4(x+1)(x-4)=144+x(-4x-4) | | u/16+15=20 | | x+x2+(10+x)=90 | | x^2-17x+124=0 | | 17=v/3+10 | | -5x+10=-90 | | 3^(x)-8=2-x | | -1-2y=-5y+5y+9 | | 1.2(6x+8)=(0.x+14) | | z/8=1=2 | | 4v+5+4=13 | | (3x-7)(5+2x)=0 | | p+10=-4p-5 | | 1/10(x+11)=-2/8-x | | 8x-6=-60 | | -3+9g=-9+10g | | p=3+0.63/0.75 | | 6h-8=-2h | | 5.88=0.75p+3 | | 8c+7=3+9c |

Equations solver categories